The Experiences of English Department Students during the Kampus Mengajar Program at Elementary School: Phenomenology Approach - Yanto Yanto; Tubagus Zam Zam Al Arif; Siti Maharani Salsabilla (Indonesian Language Education and Applied Linguistics Reviews, 2025)
The purpose of the this research is to find out the experiences of English Department Students in Jambi University while participating in the Kampus Mengajar Program at the Elementary School in Jambi Province. This research employed a qualitative method with phenomenology approach that consists of 7 participants of English Department students and are willing to participate in this research. The main source of data was an in-depth-interview and documentation that provides information or evidence related to the research. The data were analyzed by using thematic analysis developed by Braun and Clarke (2006). This research also used two theories that is The Adult Learner Theory and The Experiential Learning Theory. The findings showed that several themes from the interview. They were the motivation to join the Kampus Mengajar Program, the initial process of joining the Kampus Mengajar program, the obstacles faced during the Kampus Mengajar program, the valuable experiences during the Kampus Mengajar program, the skills that improved during the Kampus Mengajar program, and the experiences when teaching English.